Using Digital Application for Giving Feedback on Students’ Writing: A Case in Written English Classroom - Billah, Taqiyya Aliyya (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
This study investigates the use of digital applications by English teachers to provide feedback on students' written work. The research was conducted at Sunan Ampel State Islamic University in Surabaya, Indonesia. The participants were one English lecturer from the Written English A class in the 2023-2024 academic year, as well as 3rd-semester students enrolled in the class. Data was collected through interviews with the lecturer and analysis of students' written assignments that received online corrective feedback. The findings reveal that the lecturer utilized a variety of digital tools, including Google Docs, Microsoft Word, and Turnitin, to deliver feedback on students' writing. The analysis indicates that direct feedback was the most common type used, while indirect and metalinguistic feedback were employed less frequently. The digital applications facilitated the feedback process by enabling the lecturer to provide more detailed, personalized, and multi-modal feedback to support the improvement of students' writing skills. This study contributes to the understanding of how English teachers leverage technology to enhance the feedback practices in the writing classroom. The results suggest that strategic integration of digital tools can significantly improve the quality and effectiveness of feedback delivered to students on their written work